Pengaruh Waktu Inkubasi Pada Sediaan Terhadap Jumlah Telur Cacing Soil Transmitted Helminths yang Terdeteksi dengan Metode Kato Katz - Ibrahim, Indah Pratiwi; Putri, Novita Eka; Solikah, Monika Putri (Universitas Mohammad Husni Thamrin, 2025)
Soil-transmitted helminth (STH) infections remain a public health concern in tropical regions with poor sanitation. The Kato-Katz method isrecommended by the World Health Organization (WHO) for detecting helminth eggs due to its efficiency and sensitivity in both field and laboratory settings. One of the technical factors that may influence egg morphology visibility on the slide is incubation time. This study aimed to determine the effect of incubation time variation (20, 30, and 40 minutes) in a refrigerator on the number of STH eggs detected using the Kato-Katz method. This research applied an experimental design with a quantitative approach. Positive STH fecal samples were incubated at three time intervals and examined microscopically. Observations were recorded in Eggs Per Gram (EPG) and analyzed using the Shapiro-Wilk test, One-Way ANOVA, and Bonferroni post-hoc test. The average EPG increased with longer incubation times: 140.00 (20 minutes), 162.22 (30 minutes), and 262.22 (40 minutes). ANOVA showed a significant difference between groups (p = 0.000), and the Bonferroni test confirmed significant differences involving the 40-minute group. These findings indicate that 40 minutes of incubation is the most optimal duration for maximizing STH egg detection using the Kato-Katz method. Keywords: Feces, Kato-Katz, Soil-Transmitted Helminths, Helminth Eggs, Incubation Time.